1988
DOI: 10.1111/j.2044-8309.1988.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behaviour of children aged 6–11: Gender differences and their magnitude

Abstract: A total of 72 boys and 72 girls, of six age groups from 6 to 11 years, was observed in the school classroom over eight 5-minute periods, under conditions of low structure, non-directive teaching; aggressive and other categories of behaviour were recorded. There were no overall gender differences in aggression, but boys showed significantly more physical aggression than girls (overall effect size d = 0.36), whereas girls showed significantly more verbal aggression than boys (overall effect size d = 0.66). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
2
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 13 publications
(22 reference statements)
4
35
2
3
Order By: Relevance
“…Cogn Ther Res (2011) 35:199-208 205 finding supports the results from other study reports that adolescent boys have higher levels of aggression (Archer et al 1988;Bongers et al 2004;Hyde 2005;Martino et al 2008). Boys are more likely to be physically aggressive and girls tend to substitute indirect (non-confrontational) forms of aggression than more direct ones.…”
Section: Gender Differencessupporting
confidence: 91%
“…Cogn Ther Res (2011) 35:199-208 205 finding supports the results from other study reports that adolescent boys have higher levels of aggression (Archer et al 1988;Bongers et al 2004;Hyde 2005;Martino et al 2008). Boys are more likely to be physically aggressive and girls tend to substitute indirect (non-confrontational) forms of aggression than more direct ones.…”
Section: Gender Differencessupporting
confidence: 91%
“…If one assumes that these particular boys also showed higher levels of physical and direct verbal aggression than the girls, then these results are consistent with Bandura's [1973Bandura's [ , 1977 claim that the anticipated consequences of a behaviour influences its frequency of occurrence. Although Perry et al [1989] later found fewer sex differences and concluded that the results of the 1986 study were confounded by the sex of the target (with children tending to report on same-sex aggression), there is evidence to suggest that both girls and boys employ more same-sex than cross-sex aggression [e.g., Archer et al, 1988]. There is also evidence to suggest that children's friendship groups tend to consist of same-sex peers [see Daniels-Bierness, 1989].…”
mentioning
confidence: 99%
“…It was predicted that when the aggressor was a male, the participants would predict that he would use direct aggression (physical and verbal) more than when the aggressor was a female; the results confirmed this. Since previous research supports the view that indirect aggression is more typical of females [1,26,[28][29][30][31][32][33][35][36][37][38][39], and more experience with a certain behavior will enhance stereotypical beliefs between sex differences in aggressive behavior [43], it was predicted that females would be predicted to use indirect aggression more often than males, and as expected, results confirm this hypothesis; when the aggressor was a female, the adolescents predicted that the aggressor would use indirect aggression more than when the aggressor was a male.…”
Section: Discussionmentioning
confidence: 50%